Growth with responsibility in a globalised world - findings of the Shadow G-8 - Stiglitz, Joseph E. (Friedrich-Ebert-Stiftung BerlinDE, 2007)
Deals with the discussion of the Shadow G-8 meeting which centered on four themes viz. climate change, global imbalances, promoting growth and reducing poverty in the developing world (especially in Africa), and global governance.